1994
DOI: 10.1016/s0741-5214(94)70157-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leg elevation on the skin microcirculation in chronic venous insufficiency

Abstract: Leg elevation is advised in the treatment of venous disease associated with edema. We have used laser Doppler fluxmetry to assess the effects of leg elevation on the skin microcirculation. Methods: Fifteen patients with lipodermatosclerosis caused by chronic venous insufficiency and 15 control subjects were studied. Measurements were made from the liposclerotic skin of patients and 8 cm above the medial malleolus in control subjects. Laser Doppler flux, blood cell velocity, and concentration of moving blood ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 28 publications
0
48
0
2
Order By: Relevance
“…12 Published healing rates of venous ulcers obtained with compression therapy vary widely from 40-95%. [4][5][6][7][8][9][10] Unfortunately, a significant number of venous ulcers remain refractory to compression treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12 Published healing rates of venous ulcers obtained with compression therapy vary widely from 40-95%. [4][5][6][7][8][9][10] Unfortunately, a significant number of venous ulcers remain refractory to compression treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Leg elevation is effective in patients with C4 disease by increasing microcirculatory flow. 542 Although employing only a surrogate measure, a prospective study of exercise in 20 patients showed similar results in C5 patients, with an improvement in calf muscle pump function. 543 A structured review also suggested a positive effect of exercise (ambulation) on calf muscle pump function, although not directly assessed for VLU occurrence.…”
Section: Primary Preventionmentioning
confidence: 93%
“…Simple elevation of the legs above heart level for 30 minutes three or four times per day is effective in reducing edema and improving the cutaneous microcirculation in patients with CVI. 67,68 In more advanced disease, leg elevation alone will not be sufficient, and most experts consider compression stockings an essential treatment modality. 42 69,79 Compression therapy has also been shown to enhance fibrinolysis, [80][81][82] and it may be an important mechanism in reducing fibrosis and promoting ulcer healing.…”
Section: Mechanical Therapymentioning
confidence: 99%